The importance of lakes for bat conservation in Amazonian rainforests: an assessment using autonomous recorders - Torrent, Laura; López-Baucells, Adrià; Rocha, Ricardo; Bobrowiec, Paulo Estefano Dineli; Meyer, Christoph F.J. (Remote Sensing in Ecology and Conservation, 2018)
Recent studies predict a future decrease in precipitation across the tropics, particularly the Amazon, likely causing significant droughts that have negative consequences for Amazonian freshwater biomes, especially lakes. Furthermore, immediate consequences of global warming for terrestrial fauna associated with tropical lakes are poorly understood as the vast majority of studies come from temperate regions. Here, we assess the seasonal importance of lakes for the conservation of aerial insectivorous bats in the Central Amazon using passive bat recorders. We compared richness, general bat activity and foraging activity between lakes and adjacent forest. Of a total of 21 species/sonotypes recorded in both habitats, all were detected over lakes, and 18 were significantly more active over lakes than in forest. Only two species had significantly higher activity levels in the forest than at the lakes. Species richness and general bat activity over the lakes were higher in the dry than in the rainy season. Foraging activity was also greater over the lakes than within the forest in both seasons. Moreover, both variables were positively correlated with lake size, although the effect on activity was species-specific. Climate change-driven shrinking of lakes may have detrimental consequences for aerial insectivorous bats, especially for the most water-dependent species. Compared to permanent water bodies of other regions, the value of tropical lakes for functionally important taxa, such as bats, has been understudied. Higher bat activity levels over lakes than in forest in both seasons and comprising the whole ensemble of aerial insectivorous bats of the study region, indicate that lakes embedded in Amazonian terra firme forests deserve special attention for future bat conservation. © 2018 The Authors. Remote Sensing in Ecology and Conservation published by John Wiley & Sons Ltd on behalf of Zoological Society of London.